Fetomaternal Outcomes and Associated Factors among Mothers with Hypertensive Disorders of Pregnancy in Suhul Hospital, Northwest Tigray, Ethiopia - Fisseha Hailemariam Syoum; Girmatsion Fisseha Abreha; Dessalegn Massa Teklemichael; Mebrahtu Kalayu Chekole (Journal of Pregnancy)
Background. Hypertensive disorder of pregnancy is the leading cause of maternal and perinatal morbidity and mortality worldwide and the second cause of maternal mortality in Ethiopia. The current study is aimed at assessing fetal-maternal outcomes and associated factors among mothers with hypertensive disorders of pregnancy complication at Suhul General Hospital, Northwest Tigray, Ethiopia, 2019. Methods:A hospital-based cross-sectional study was conducted from Oct. 1st, 2019, to Nov. 30, 2019, at Suhul General Hospital women’s chart assisted from July 1st, 2014, to June 31st, 2019. Charts were reviewed consecutively during five years, and data were collected using data abstraction format after ethical clearance was assured from the Institutional Review Board of Mekelle University College of Health Sciences. Data were entered into Epi-data 3.5.3 and exported to SPSS 22 for analysis. Bivariable and multivariable analyses were done to ascertain fetomaternal outcome predictors. Independent variables with p value < 0.2 for both perinatal and maternal on the bivariable analysis were entered in multivariable logistic regression analysis and the level of significance set at p value < 0.05. Results. Out of 497 women, 328 (66%) of them were from rural districts, the mean age of the women was 25.94±6.46, and 252 (50.7%) were para-one. The study revealed that 252 (50.3%) newborns of hypertensive mothers ended up with at least low Apgar score 204 (23.1%), low birth weight 183 (20.7%), preterm gestation 183 (20.7%), intensive care unit admissions 90 (10.2%), and 95% CI (46.1% -54.9%), and 267 (53.7%) study mothers also developed maternal complication at 95% (49.3-58.1). Being a teenager (AOR=1.815: 95%CI=1.057−3.117), antepartum-onset hypertensive disorders of pregnancy (AOR=7.928: 95%CI=2.967−21.183), intrapartum-onset hypertensive disorders of pregnancy (AOR=4.693: 95%CI=1.633−13.488), and low hemoglobin level (AOR=1.704: 95%CI=1.169−2.484) were maternal complication predictors; rural residence (AOR=1.567: 95%CI=1.100−2.429), antepartum-onset hypertensive disorders of pregnancy (AOR=3.594: 95%,CI=1.334−9.685), and intrapartum-onset hypertensive disorders of pregnancy (AOR=3.856: 95%CI=1.309−11.357) were predictors of perinatal complications. Conclusions. Hypertensive disorder during pregnancy leads to poor fetomaternal outcomes. Teenage age and hemoglobin levels were predictors of maternal complication. A rural resident was the predictor of poor perinatal outcome. The onset of hypertensive disorders of pregnancy was both maternal and perinatal complication predictors. Quality antenatal care services and good maternal and childcare accompanied by skilled healthcare providers are essential for early detection and management of hypertensive disorder of pregnancy.